Integrasi Artificial Intelligence dalam Pengembangan SDM Perguruan Tinggi Era Society 5.0: Systematic Literature Review: Indonesia - Cindy Fionna; Ardella Febri Dwi Syaharani; Amellia Enggellina; Bela Maulana (Pusat Riset dan Inovasi Nasional, 2026)
Artificial Intelligence is the foundation of the automation revolution in the society 5.0 era, which requires universities to be ready to transform in the use of artificial intelligence as a pedagogy. This study applies the Systematic Literature Review (SLR) method, which aims to critically review the human resources development strategies in universities in using artificial intelligence for digital competencies in the society 5.0 era, focusing on artificial intelligence training, ethical, and digital leadership. Based on the results of the systematic literature review, the researchers idenetified 27 selected journal articles, both national and international, to be analyzed descriptively. The findings of this study indicate that pedagogy-based artificial intelligence training supports universities learning in the context of digital transformation. The use of artificial intelligence must adhere to ethics that uphold transparency, accountability, and prevent plagiarism, and digital leadership must formulate a concrete vision in fostering an innovation culture. Thus, successful artificial intelligence integration is strongly supported by a well-established institutional framework.